Content of cytokine inflammatory markers in patients with chronic heart failure caused by cardiomyopathy - K. A. Khamitova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The present article discusses the characteristics and significance of content violation of key pro-inflammatory cytokines IL-8, TNFa, MCP-1 and key anti-inflammatory cytokine IL-10 during pro-inflammatory stage in patients with chronic heart failure (CHF), determined by dilated cardiomyopathy (31 patient) and in CHF patients with coronary heart disease (CHD) (29 patients). EIA method with enzyme immune test systems (ZAO "Vector Best") and analyser ACCESS was used to assess the content of cytokines in the blood. The results of the study showed significant reduction of IL-8, increase of TNFa, MCP-1 and IL-10. Violation of adequate response of cytokines in pro-inflammatory stage enables to consider this disorder as a pathogenic unfavorable factor, leading to CHF progression in patients with dilated cardiomyopathy and CHD. Comparison of the parameters of cardiac hemodynamics, differential white blood cell count and correlation results proves that heart failure in patients with dilated cardiomyopathy and CHD have similar pathogenic origins of chronic inflammatory process. Imbalance of IL-8, TNFa, MCP-1 and IL-10 does not provide protection from inflammatory and bacterial antigens. In case of inadequate and protracted inflammatory reaction, decreased cytokine-producing leukocyte function can destroy myocardium. Results of correlation analysis prove violation of linear connection andformation of atypical correlations between TNFa and TNFa monocytes and neutrophils, IL-8 and monocytes, TNFa and IL-10, IL-10 and lymphocytes, IL-10 and TNFa, IL-8 and IL-10. Increased production of TNFa, MCP-1 in combination with decreased IL-8 and increased IL-10 indicates staging violation accompanied by delay of transition of pro-inflammatory stage into anti-inflammatory one.